EFFECTS OF GLOBALIZATION ON THE PERFORMANCE OF SMALL AND MEDIUM ENTERPRISES IN THE TEXTILE INDUSTRY IN KENYA (A CASE OF RICARDO (EPZ) INTERNATIONAL KENYA) - CHRISTINE, MWANIKI ANN (IJRDO - Journal of Business Management, 2015)
Globalization has opened economies locally and internationally increasing cross border trade and investments, thus spurring the competition. This has however, inserted pressure on the small and medium enterprises, especially in the textile industry in Kenya, whose performance is currently very poor. The purpose of this study was to analyze the effects of globalization on the performance of SMEs in the textile industry in Kenya. The sample size was determined using stratified sampling and the sample population for this study will consist of 105 preselected employees from Ricardo (EPZ) International. The study adopted exploratory and descriptive research designs. Structured questionnaires were used in this study to collect primary data. Quantitative data collected was analysed using descriptive statistics by the help of SPSS (V. 20) which is the latest version, and presented through frequencies, percentages, means and standard deviations in tables, figures and charts and in addition, multiple regressions used to establish the relationship between the dependent and the independent variables. The results have shed light on the state of performance of SMEs practice and use of local organizations in this area, and show currently adopted technologies and the barriers that prevent their optimization. The findings show that there is a need for support for the SMEs to enhance their Performance. Creation of more widespread awareness about globalization, better provision of the requisite technologies, as well as adequate training and skills upgrading and updating are some of the support that would help SMEs plan strategically. The results clearly indicate the need to provide support to SMEs if they are to successfully manage globalization and benefit from it. Accordingly, support to overcome the identified barriers of globalization need to be recognized.